2005
DOI: 10.1177/104990910502200107
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary resuscitation is not addressed in the admitting medical records for the majority of patients who undergo CPR in the hospital

Abstract: Cardiopulmonary resuscitation (CPR) is routinely performed on patients who develop cardiopulmonary arrest in the hospital. In some situations, it is performed on terminally or critically ill patients where death is predicted to be inevitable despite CPR. Since prior consent is not required for this procedure, CPR may be performed without patient consent or foreknowledge. Many of these patients may not want CPR if the anticipated outcome is reviewed with them. This study investigated the frequency of occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…In one study, Mirza and colleagues identified that CPR was not addressed in the admitting medical records for 76% of patients who underwent CPR during hospitalization. 21 These findings underscore the critical need for interventions to promote code status discussions and ensure the delivery of patient-concordant care at the EOL. For example, ‘the presumed full code’ option may not be an appropriate code status order throughout a patient’s hospitalization.…”
Section: Discussionmentioning
confidence: 93%
“…In one study, Mirza and colleagues identified that CPR was not addressed in the admitting medical records for 76% of patients who underwent CPR during hospitalization. 21 These findings underscore the critical need for interventions to promote code status discussions and ensure the delivery of patient-concordant care at the EOL. For example, ‘the presumed full code’ option may not be an appropriate code status order throughout a patient’s hospitalization.…”
Section: Discussionmentioning
confidence: 93%
“…Please be specific. 6. Should you describe what happens after a cardiac arrest (assuming resuscitation was successful)?…”
mentioning
confidence: 97%
“…Many patients do not want to discuss CPR with their physician, 1,2 and many physicians feel that they do not have the time or training to discuss this issue properly. 3,4 As a result, many seriously or terminally ill patients receive CPR and advanced life-sustaining measures without prior discussion and informed consent, [5][6][7] even though a large proportion may wish to forego CPR. 2 In order to help with the process of communication, many authors have published effective communication techniques (i.e., the style of communication).…”
mentioning
confidence: 99%
“…[29][30][31][32] As a result, many terminally ill patients receive care that is not consistent with their wishes, and many are admitted to the ICU without a proper discussion of the alternatives (e.g., palliative care), 31,33,34 which leads to patient dissatisfaction and increased use of ICU resources. 35,36 This underscores the need for skill and delicacy whenever a physician discusses goals of care.…”
mentioning
confidence: 99%